(untitled) (Veterinary Science, 2017)
A sample of fifty six (56) farms of fattening of cows was analyzed in Quemú- Quemú department with the objective to establish the global, asignative and Farrell efficiency. The function of production and cost was decided at first, two functions of kind Cobb-Douglas, obtaining (R2) above than 90% were proposed in every case. From the function Cobb-Douglas, the absolute frontier of Greene and the middle functions of Marschak-Andrews were determinate, establishing the indexes of technical efficiency (IET, IECT) and technological efficiency (IdD). The indexes related at first were determinate, to establish the global and asignative efficiency, from the location index (IdL). After and from the IdL values the farms by levels were assembled, to establish curves of levels related to the production function (isocuantas) and cost function (isocostes); the difference between levels indicate the level of global and assignative efficiency of the farms. At last the opinion about assignative and global efficiency was intercepted with the objective to establish a classification of the farms, according to Farrel’s methodology. These analyses allow concluding about the heterogeneity of the system, establishing three subsystems of pastoral characteristic but with different technological levels, named as: competitive, pre-competitive and non-competitive